Mastery motivation as a predictor of occupational performance following upper limb intervention for school-aged children with congenital hemiplegia - Miller, L.; Ziviani, J.; Ware, R.; Boyd, Roslyn (2014)
© 2014 Mac Keith Press. Aim: To determine the extent to which children's mastery motivation predicts occupational performance outcomes following upper limb intervention (ULI). Method: In this cohort study, participants received 45 hours of ULI, either in an intensive group-based or distributed individualized model. The Dimensions of Mastery Questionnaire (DMQ) measured mastery motivation at baseline. Occupational performance outcomes were assessed at baseline and 13 weeks' post-intervention using the Canadian Occupational Performance Measure (COPM). Multivariable models determined the contribution of mastery motivation to COPM outcome irrespective of group membership. Results: Forty-two children with congenital hemiplegia (29 males, 13 females; mean age 7y 8mo [SD 2y 2mo]; range 5y 1mo-12y 8mo; Manual Ability Classification System [MACS] I=20 and II=22; predominant motor type unilateral spastic n=41) participated in the study. Significant gains were seen in COPM performance and satisfaction scores (p<0.001) post-intervention with no between group differences. Children who had greater persistence with object-oriented tasks (p=0.02) and better manual ability (p=0.03) achieved higher COPM performance scores at 13 weeks. Children's persistence on object-oriented tasks was the strongest predictor of COPM satisfaction (p=0.01). Interpretation: Children's persistence with object-oriented tasks as well as manual abilities needs to be considered when undertaking ULI. Predetermining children's motivational predispositions can assist clinicians to tailor therapy sessions individually based on children's strengths, contributing to effective engagement in ULI.